Umberto Eco’s Encyclopedia vs. Porphyry’s Tree - Cornea, Andrei (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2009)
AbstractThe paper questions the postmodern, wide-spread tendency to abusively reconstruct the meaning of some texts of the philosophers of the past, so that they may serve as allies or foes in our own contemporary ideological wars. The chosen example is an article by Umberto Eco, called “Anti-Porphyry”, and the parallel chapter, “Dictionary vs. Encyclopedia”, from his well-known book Semiotics and the Philosophy of Language. According to Eco, the famous “Porphyry’s tree” is the pictorial representation of the so-called “strong thought”, which — so he believes — was being subverted from the outset in the benefit of the “weak thought” or “Encyclopedia thought” even in the works of some essentialist philosophers like Aristotle or St. Thomas Aquinas. On the other hand, Eco thinks he found in d’Alembert’s Discours préliminaire to the French Encyclopédie a forerunner of postmodern “weak thought”, which resembles the so-called 3rd type labyrinth or the “rhizome” described by G. Deleuze, and which is the opposite of the logic encapsulated in the “Porphyry tree”. The paper attempts to show that Eco distorted the ideas of the above-mentioned philosophers by dislodging them from their original metaphysical context and by manipulating some of the relevant texts. So, in Eco’s view, both Aquinas and d’Alembert anachronistically became forerunners of postmodernism. In fact, what Eco eventually got was less an accurate description of some philosophies of the past, than a historical-philosophical reconstruction rather abusively legitimizing his own ideas.